2023
DOI: 10.1038/s41588-023-01442-7
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase II dynamics shape enhancer–promoter interactions

Abstract: How enhancers control target gene expression over long genomic distances remains an important unsolved problem. Here we studied enhancer-promoter contact architecture and communication by integrating data from nucleosome-resolution genomic contact maps, nascent transcription, and perturbations to transcription-associated proteins and thousands of candidate enhancers. Contact frequency between functionally validated enhancer-promoter pairs was most enriched near the +1 and +2 nucleosomes at enhancers and target… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 125 publications
5
27
0
Order By: Relevance
“…We observe an approximately 2-fold increase in extruded loop size comparing quiescent chromatin to active chromatin, and this effect is similarly observed when examining the impact of H3K27ac and RNAPII binding. Our finding that RNAPII binding obstructs cohesin-mediated loop extrusion is consistent with two recent studies that investigated RNAPII’s impact on cohesin through RNAPII and enhancer perturbations 35 as well as polymer simulations, CTCF depletion, and Wapl knockout experiments 36 . These substantial differences in average extruded loop size observed for different levels of RNAPII binding and H3K27ac suggest that gene and enhancer activity obstruct cohesin-mediated loop extrusion.…”
Section: Discussionsupporting
confidence: 92%
“…We observe an approximately 2-fold increase in extruded loop size comparing quiescent chromatin to active chromatin, and this effect is similarly observed when examining the impact of H3K27ac and RNAPII binding. Our finding that RNAPII binding obstructs cohesin-mediated loop extrusion is consistent with two recent studies that investigated RNAPII’s impact on cohesin through RNAPII and enhancer perturbations 35 as well as polymer simulations, CTCF depletion, and Wapl knockout experiments 36 . These substantial differences in average extruded loop size observed for different levels of RNAPII binding and H3K27ac suggest that gene and enhancer activity obstruct cohesin-mediated loop extrusion.…”
Section: Discussionsupporting
confidence: 92%
“…14,15,60,61 In this sense, we observed that cohesin is accumulated at ERα-mediated contact points upon TOP2B depletion, suggesting that these supercoiling-mediated contacts would be also associated with the cohesin complex, either as de novo loading to stabilize the interactions, or as part of a supercoiling-driven loop extrusion mechanism. ERα binding, either on its own or in conjunction with RNA Pol ll, 16,17 could also help to shape regulatory contacts by representing an impediment for the spreading of supercoiling and/or cohesin movement, which would explain its preferential location at these contact points. The combination of increased supercoiling levels with the appearance or strengthening of barriers for its spreading would constitute an ideal scenario for the rewiring of long-range chromatin interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The link between RNAPolII and looping has been debated, with conflicting results linked to low-resolution datasets or pharmacological agents with non-specific indirect effects 22,31,32,[39][40][41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, two studies employed a degron to achieve short-term RNAPolII degradation and uncovered a previously underappreciated effect on E-P loop maintenance 31,32 . Here, we build on these works by creating genome-wide maps of cell type-invariant and cell type-specific chromatin loops during the transitions from hiPSCs to NPCs and NPCs to post-mitotic neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation